2022
DOI: 10.1155/2022/3723680
|View full text |Cite
|
Sign up to set email alerts
|

Study on Decarburization Mechanism and Law of GCr15 Bearing Steel during Heat Treatment

Abstract: In order to understand the effects of heating temperature and holding time on decarburization of GCr15 bearing steel, an experimental device for heat treatment of bearing steel was designed and the sample was heated and held by a tubular heating furnace. The microstructure and depth of decarburized layer of bearing steel under various working conditions were observed and measured by a metallographic microscope. The results show that the total decarburization depth increases with the increase of temperature; al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The essence of bearing steel heat treatment is to control its microstructure by controlling the temperature change process of bearing steel. For example, the transformation rate of inclusions is affected by temperature [26], and the variation in holding time is related to the decarburization of bearing steel [27]. Therefore, the precise measurement and control of temperature are key to ensuring the quality of heat treatment of bearing steel.…”
Section: Heat Treatment Process Of Bearing Steel Based On Digital Twinmentioning
confidence: 99%
“…The essence of bearing steel heat treatment is to control its microstructure by controlling the temperature change process of bearing steel. For example, the transformation rate of inclusions is affected by temperature [26], and the variation in holding time is related to the decarburization of bearing steel [27]. Therefore, the precise measurement and control of temperature are key to ensuring the quality of heat treatment of bearing steel.…”
Section: Heat Treatment Process Of Bearing Steel Based On Digital Twinmentioning
confidence: 99%
“…As the depth of the decarburized layer increases, the fatigue limit of the material decreases [23]. Additionally, the decarburized layer changes the damage mechanism of the rail steel and influences the surface microstructure, hardness, wear, and fatigue resistance [24,25]. It has been observed that the reduction of the decarburized layer positively affects the material's fatigue resistance and service performance [26,27].…”
Section: Introductionmentioning
confidence: 99%